The implementation of a bilingual-bicultural literacy intervention programme for deaf learners in Namibia - Bruwer, Beausetha Juhetha (University of the Free State, 2021)
The Bilingual-Bicultural approach is considered the best approach to teach deaf learners. This approach also provides the best opportunity for deaf learners to become biliterate. Namibia too has adopted the Bilingual-Bicultural approach to teaching deaf learners and are a signatory to national and international policies and laws to ensure deaf learners are provided with the best opportunity for an education. Contrary to the adoption of the Bilingual-Bicultural approach, policies and laws, no impact has been seen on an improvement in the deaf learners’ academic performance. Deaf learners still leave school with low literacy levels and unsure of their future. The main purpose of this study was to find the best instructional practices to teach deaf learners through the Bilingual-Bicultural approach. This was done through the implementation of an intervention programme that can narrow the delay and gap in language learning and literacy. The study adopted a programme evaluation within a multi-method research design. The research objectives accommodated the implementation of a Bilingual-Bicultural literacy intervention programme for deaf learners. The data for the study consisted of quantitative data in the form of measurements based on diagnostic tests and qualitative data in the form of document analysis, participant and non-participant observations as well as unstructured interviews. The variety of data directed the study to a multi-data analysis. The themes that were established for feedback of the research findings originated from the research objectives and the programme evaluation questions that were drawn up to guide the evaluation of the Bilingual-Bicultural literacy programme. The emphasis of the intervention programme was to draw up new and adopted Integrated Planning Manuals that are based on the NSL and Written English syllabuses and prescribed language skills of both language subjects. From the new IPMs, lessons were designed for both language subjects. Teaching and learning materials were also designed to support the lessons. The programme envisaged a systematic method of learning the deaf learners the two languages at the same time. The aim was to teach Written English based on NSL. The programme had a dual integrated approach in that it integrated into specific themes and topics for a week and the language skills for each language subject. It also integrates into the other subjects that are taught to the learners. The programme was systematic in teaching learners in small portions, every time building on these small portions. Teachers were provided with deliberate training on the instructional practices that were intended for the programme. The implementation of the Bilingual-Bicultural literacy programme resulted in a positive impact and improvement on the biliteracy of the deaf learners. Statistical analyses underscored the value of the intervention program. T-tests yielded statistical significant results for both NSL and Written English skills with regard to the total scores as well as the sub-tests included in this study (p<0.05). The teachers who participated in the study showed significant teacher attributes in the form of self-efficacy, the ability to communicate in NSL, experience and skills to teach deaf learners and good teacher-learner relationships. Even though, through the programme, the teachers gained pedagogical knowledge and understanding to applicable instructional practices that can be implemented in their teaching, they lacked support systems to sustain their instruction. Continuous interaction and support are thus recommended at all levels to sustain the further development of the Bilingual-Bicultural literacy programme.
Thesis (Ph.D. (Afro-Asiatic Studies, Sign Language and Language Practice))--University of the Free State, 2021
Keywords: Bilingual-Bicultural; Biliteracy; Bilingual Education; Bimodal; Translanguaging; Deaf Education; Junior primary; Namibian Sign Language (NSL); Written English; Deaf learner; Deaf adults; Deaf Culture; School for deaf learners